Population and Home Range of Javan-hawk Eagle (Spizaetus bartelsi Stresemann, 1924) at Mount Kendeng, Cikaniki Resort, Gunung Halimun National Park - Tri Widodo; Jarwadi Budi Hernowo; Kuswandono . (Department of Forest Resources Conservation and Ecotourism - IPB University, 2004)
Population and home range study of javan-hawk eagle (Spizaetus Bartelsi Stresemann, 1924) was conducted from Februari 2003 until July 2003 at Mount Kendeng Cikaniki Resort (± 8.5 km2), Gunung Halimun National Park, West Java. Indonesia. There were 11 individu of javan-hawk eagles observed from 5 station specified as monitoring plots, consisted of 8 adults and 3 youngs. Individual density of javan-hawk eagle was about 0. 77 km2/individu. The pairs density at around 2.83 km2/pairs and sex ratio was close to 1 : 1. Javan-hawk eagle in this area was distributed al Mount Kendeng area. Mount Andam, and about Nirmala tea plantation. Habitat type in Mount Kendeng can be grouped as a natural forest (tropical rain forest), border between natural forest and tea plantation, tea plantation, countrifield (resident settlement) and also the agriculture form (rice field). The habitat characteristics of javan hawk eagle were as follows : natural forest with high variety of fauna (abundance of food sources), hilly area, a river stream presence, and the natural forest can give its function as a food supply, nesting area, mating, and shelter. Home range for Pengkeh (male adult of javan-hawk eagle) in mount Kendeng was around+ 3.06 km2, and its pair of Pengkeh (female adult of javan-hawk eagle) was about+ 1.69 km2, meanwhile home range of Juvenex (young of javan-hawk eagle) was close to± 1.31 km2 and or the No Molt 2 (male adult of javan-hawk eagle) in mount Andam was about± 2./9 km2. The hunting area for Pengkeh was about+ 0.31 km2, pair of Pengkeh were ± 0.13 km2, Juvenex was ± 0.19 km2 and/or the No Molt 2 was about± 0.13 km2. At the/air weather condition, a lot of perch activity was seen al 08.30 a.m-11.00 a.m and 11.30 a.m-02.20 p.m, while a lot of flying activity was seen at 08.30 a.m- 11.00 a.m and 12.00 a.m-0/.20 p.m. Keywords: javan-hawk eagle. population, home range, daily activity